2001
DOI: 10.1016/s0924-9338(01)00579-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathological predictors of suicide in patients with major depression during a 5-year follow-up

Abstract: These symptoms seem to be helpful early predictors for the risk of suicide during the further course of illness. This should be taken into account for suicide prevention in the course of major depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 29 publications
1
62
1
2
Order By: Relevance
“…This study design takes maximum advantage of the unique strengths of VA data resources and has distinct advantages when studying rare outcomes, such as suicide. 34,35 The study observation period for our cohort began on April 1, 1999, and extended until the end of fiscal year 2004 (September 30, 2004). Observations from 1997 to 1999 were not included in the study cohort, because of a lack of national pharmacy data prior to 1999.…”
Section: Methodsmentioning
confidence: 99%
“…This study design takes maximum advantage of the unique strengths of VA data resources and has distinct advantages when studying rare outcomes, such as suicide. 34,35 The study observation period for our cohort began on April 1, 1999, and extended until the end of fiscal year 2004 (September 30, 2004). Observations from 1997 to 1999 were not included in the study cohort, because of a lack of national pharmacy data prior to 1999.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies confirmed the risk of suicide to be particularly high in hospitalized depressed patients (4)(5)(6). Profound hopelessness, hypochondriacal ruminations or delusions, and thoughts of suicide or self-harm during depression predict future suicide (7).…”
mentioning
confidence: 87%
“…This confirms findings from a psychological autopsy study by Isometsa et al in which 79% of the suicides studied occurred during depressed or mixed states. 37 In studies with mixed samples (patients with bipolar disorder and major depression), three prospective studies found that suicidal ideation predicted completed suicide, [38][39][40] but others found that suicidal ideation was not a predictor, despite being more prominent in patients with previous attempts, 41 Oquendo et al suggests that measures of suicidal ideation can be more useful to identify patients at higher risk of suicide behavior when integrated into a "pessimism factor" which encompasses measures of subjective depression, reasons for living and hopelessness rather than a single predictor of suicidal behavior. 18 In conclusion, although suicide ideation has been understudied until recently, it can be an important risk factor for suicide attempts.…”
Section: Stress-diathesis Modelmentioning
confidence: 99%